(untitled) (Caderno Espaço Feminino, 2019)
Filiados à Análise de Discurso (Pêcheux), propomos uma análise dos dizeres sobre a mulher presentes no romance português A dama pé de cabra, que se atualizam nos jornais jornalístico (online), para compreendermos o lugar dessa memória sobre a mulher na esfera social. PALAVRAS-CHAVE: Análise de Discurso. Mídia. Mulher. Memória. ABSTRACT In the light of the theoretical assumptions of Discourse Analysis (Pêcheux), we propose an analysis of the discourses about women, present on the Portuguese novel The lady of the goat, and updated in online journalistic discourse, in order to understanding of the imaginary about women on the social sphere. KEYWORDS: Discourse Analysis. Media. Woman. Memory.